2020
DOI: 10.3390/min10020100
|View full text |Cite
|
Sign up to set email alerts
|

A New Reference for the Thermal Equation of State of Iron

Abstract: The high-pressure, high-temperature behavior of iron was investigated to 140 GPa and 3500 K with in situ synchrotron X-ray diffraction. Iron samples were compressed in diamond-anvil cells and heated up with the double-sided laser-heating system installed at the high-pressure ID27 of the European Synchrotron Radiation Facility (ESRF). Three different structures, namely α-bcc, γ-fcc or ε-hcp Fe were identified as a function of pressure and temperature in the domain we explored. At pressures above 90 GPa, it is c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
27
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(37 citation statements)
references
References 37 publications
8
27
2
Order By: Relevance
“…A comprehensive comparison of the equations of state parameters K 0 and K 0 ′ of the different alloys considered here is illustrated in the inset in Figure 2a. The data published by Dewaele et al (2006), Sakai et al (2014), Yang et al (2019), and Miozzi, Matas, et al (2020) for pure Fe and by Edmund et al (2019) and Yang et al (2019) for Fe-Si and Fe-C alloys, respectively, were reevaluated in order to obtain the variance-covariance matrixes (Angel, 2000) and to construct the confidence ellipses (Table 1; inset Figure 2a). The confidence ellipses of our data set are larger than those reported in the literature.…”
Section: Comparison Of Fe-c-si Alloysmentioning
confidence: 99%
See 2 more Smart Citations
“…A comprehensive comparison of the equations of state parameters K 0 and K 0 ′ of the different alloys considered here is illustrated in the inset in Figure 2a. The data published by Dewaele et al (2006), Sakai et al (2014), Yang et al (2019), and Miozzi, Matas, et al (2020) for pure Fe and by Edmund et al (2019) and Yang et al (2019) for Fe-Si and Fe-C alloys, respectively, were reevaluated in order to obtain the variance-covariance matrixes (Angel, 2000) and to construct the confidence ellipses (Table 1; inset Figure 2a). The confidence ellipses of our data set are larger than those reported in the literature.…”
Section: Comparison Of Fe-c-si Alloysmentioning
confidence: 99%
“…This might be due to the different pressure and volume uncertainties, how these are taken into account in the analysis, and to the number and range of measured pressure points in the different studies. Here, both pressure and volume uncertainties were weighted, whereas most of the (Edmund et al, 2019;Yang et al, 2019) and reference EoS for pure Fe (Dewaele et al, 2006;Miozzi, Matas, et al, 2020;Sakai et al, 2014;Yang et al, 2019) are shown for comparison. Inset: confidence ellipses centered on each data point, representing the 68.3% confidence level.…”
Section: Comparison Of Fe-c-si Alloysmentioning
confidence: 99%
See 1 more Smart Citation
“…Measured volumes of quenched hcp Fe collected in this study are presented in Figure 2 and are systematically larger, over the whole pressure range, than those of pure hcp Fe from literature (e.g. Dewaele et al, 2006;Miozzi et al, 2020). Although Si shows a large solubility in hcp Fe under high pressure, up to ~18 at % Si (e.g.…”
Section: Subsolidus Phase Relations and Equations Of Statementioning
confidence: 70%
“…Green triangles represent the experimental data from this study, purple line the EoS fitted with the elastic parameter of pure Fe, black squares the experimental data on Fe-9.5 at % Si from . Blue dashed line the EoS of pure Fe (hcp) from (Miozzi et al 2020). Inset: Ternary Fe-Si-C diagram showing the phase relations in the iron rich side.…”
Section: Subsolidus Phase Relations and Equations Of Statementioning
confidence: 99%